Alpha-1 Antitrypsin Deficiency: Home Therapy - Annunziata, Anna; Lanza, Maurizia; Coppola, Antonietta; Andreozzi, Paolo; Spinelli, Sara; Fiorentino, Giuseppe (Frontiers in Pharmacology, 2021)
While available in only a few countries, home therapy is a possible strategy for treatment of alpha-1 antitrypsin deficiency. We want to describe our experience in the management of human alpha-1 antitrypsin using home care intravenous augmentation therapy during this emergency period caused by SARS-CoV2 infection. We assessed the safety of home treatment and the quality of life of patients enrolled in the program.